2021
DOI: 10.1093/nargab/lqab043
|View full text |Cite
|
Sign up to set email alerts
|

A map of the SARS-CoV-2 RNA structurome

Abstract: SARS-CoV-2 has exploded throughout the human population. To facilitate efforts to gain insights into SARS-CoV-2 biology and to target the virus therapeutically, it is essential to have a roadmap of likely functional regions embedded in its RNA genome. In this report, we used a bioinformatics approach, ScanFold, to deduce the local RNA structural landscape of the SARS-CoV-2 genome with the highest likelihood of being functional. We recapitulate previously-known elements of RNA structure and provide a model for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
94
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(97 citation statements)
references
References 85 publications
3
94
0
Order By: Relevance
“…We see that Stem 1 is highly conserved, with deletions in the 3′ strand in only one distant coronavirus. Moreover, subsequent covariation analysis using R-scape 43 (see Methods ) detects 2 strong covarying base pairs (colored by nucleotide in Figure 2 , i.e., green A, blue U, orange C, and red G), also found in the phylogenetic analysis by Andrews et al 24 Many deletions are found in Stem 3 and the sequences are less conserved, suggesting different locations and lengths for Stem 3 in different coronaviruses. Stem 2 is the shortest and the most flexible.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…We see that Stem 1 is highly conserved, with deletions in the 3′ strand in only one distant coronavirus. Moreover, subsequent covariation analysis using R-scape 43 (see Methods ) detects 2 strong covarying base pairs (colored by nucleotide in Figure 2 , i.e., green A, blue U, orange C, and red G), also found in the phylogenetic analysis by Andrews et al 24 Many deletions are found in Stem 3 and the sequences are less conserved, suggesting different locations and lengths for Stem 3 in different coronaviruses. Stem 2 is the shortest and the most flexible.…”
Section: Resultsmentioning
confidence: 54%
“…Several works have experimentally scanned RNA genomes with windows of variable lengths. 24 , 37 , 46 In secondary structure predictions of RNAs, 120 nt is considered reasonable for predictions. 47 , 48 Indeed, in our application of five 2D folding programs that can predict pseudoknots (PKNOTS, 49 NUPACK, 50 IPknot, 51 ProbKnot, 52 and vsfold5 53 ) to four RNAs with pseudoknots, we find that the 120 nt window recommended in the literature appears reasonable in general ( Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2C); this stability value is found to be unusually low given the AU-rich nucleotide composition, suggesting that it arose through an evolutionarily-driven process; indeed, the thermodynamic Z-score was -5.5 (meaning that the WT sequence is more than 5 standard deviations more stable than random). In addition, a comprehensive analysis of RNA structural motifs in SARS-CoV-2 found that this hairpin is one of the few (nine) that show evidence of statistically significant sequence covariation — a feature of evolutionary conservation (21). The formation of the hairpin is also in agreement with previously-reported structure probing reactivity datasets (22-25), where the only reactive nucleotides occur in loop regions.…”
Section: Resultsmentioning
confidence: 99%
“…B) Location of vmiR-5p and viRNA-3p annotated on an alignment of coronavirus reference sequences. The hairpin base pairs are indicated by arcs above the sequence alignment with the two previously identified covarying base pairs (21) indicated in green. Alignment and base pairs visualized using the program R-CHI (76).…”
Section: Supplementary Figuresmentioning
confidence: 99%